The Role of Industrial, Agricultural, and Household Economic Activities in The Formation of a Green Economy in East Java: Determinants from a Spatial Perspective - Yongky Choirul Anam; Deltha Airuzsh Lubis; Ragdad Cani Miranti (Kantor Perwakilan Bank Indonesia Provinsi Jawa Timur, 2025)
This paper aims to evaluate spill-over effects of green economic growth and the role of driving factors across 38 districts in East Java. Using the 2018-2022 period, this paper measures Green Total Factor Productivity (GTFP) as the proxy of green economic development at sub-national level in East Java, while ICT index, fiscal-related policy, environmental regulation, and foreign direct investment are applied as the determinants of green growth. Emission in GTFP levels are the impact of household activities, the agricultural sector, and the processing industry. We find the persistence and appealing pattern of GTFP over the time, indicated by the increasing number of districts which generate green productivity index over. The results show the existence of spatial dependence and spatial-spillover effect in terms of green economic development in East Java, meaning that the increasing index of green productivity in a district tends to increase green productivity in neighboring regions. However, there are considerable differences of determinants which affect green productivity across districts in East Java. From spatial heterogeneity perspectives, we evaluate that each group of regions are affected by the different factors. Looking from policy perspectives, our findings suggest that one-size-fits-all policy is not proposed for promoting equal green growth across East Java districts. Instead, augmenting different treatments and policies based on spatial heterogeneity are more demanded to be applied.